2017
DOI: 10.1093/mnras/stx674
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the rotational properties of magnetic chemically peculiar stars

Abstract: The magnetic chemically peculiar (mCP) stars of the upper main sequence exhibit strong, globally organized magnetic fields that are inclined to the rotational axis and facilitate the development of surface abundance inhomogeneities resulting in photometric and spectroscopic variability. Therefore, mCP stars are perfectly suited for a direct measurement of the rotational period without the need for any additional calibrations. We have investigated the rotational properties of mCP stars based on an unprecedented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 73 publications
12
66
5
Order By: Relevance
“…The rotational period distribution is in very good agreement with the literature (e.g. Renson & Manfroid 2009;Netopil et al 2017) and shows the typical peak distribution in the 0.0 < log(P[d]) < 0.5 bin. We note that because of the time span and characteristics of the here employed photometric time-series data, we will have missed very slowly rotating ACV variables with periods of several years or more (Mathys 2017).…”
Section: Colour-magnitude Diagramsupporting
confidence: 88%
“…The rotational period distribution is in very good agreement with the literature (e.g. Renson & Manfroid 2009;Netopil et al 2017) and shows the typical peak distribution in the 0.0 < log(P[d]) < 0.5 bin. We note that because of the time span and characteristics of the here employed photometric time-series data, we will have missed very slowly rotating ACV variables with periods of several years or more (Mathys 2017).…”
Section: Colour-magnitude Diagramsupporting
confidence: 88%
“…We found that one, TIC 410451777 (HD 66295) is classified as B8/9p Si by Hartoog (1976). The rotation period is known to be 2.45 d (Netopil et al 2017) which is significantly different from what we find for TIC 410451752. The other stars in the region have no rotation period reported in the literature.…”
Section: Contamination and Multiplicitycontrasting
confidence: 85%
“…randomly distributed inclination angles (Netopil et al 2017), rotationally induced variability should be readily detectable with the employed data in this study. However, we were not able to detect variability with a statistically significant amplitude for any of our sample stars.…”
Section: Discussionmentioning
confidence: 82%